Variations of bacteria and fungi in PM2.5 in Beijing, China. (January 2018) - Du, Pengrui; Du, Rui; Ren, Weishan; Lu, Zedong; Zhang, Yang; Fu, Pingqing
Abstract: Bacteria and fungi present in the airborne fine particulate matter (PM2.5 ) play important roles in the atmosphere and provide significant impacts on human health. However, variations in the species composition and community structure have not been well understood. In this study, we sampled PM2.5 in suburban Beijing and analyzed the bacterial and fungal composition during different seasons and at different air pollution levels using gene sequencing methods. The results showed that the species richness and diversity of bacterial communities displayed a downtrend with the aggravation of air pollution. Additionally, the bacterial communities in spring samples showed the highest species richness, with average richness estimators, ACE and Chao 1, up to 14, 649 and 7608, respectively, followed by winter samples (7690 and 5031, respectively) and autumn samples (4368 and 3438, respectively), whereas summer samples exhibited the lowest average ACE and Chao 1 indexes (2916 and 1900, respectively). The species richness of fungal communities followed the same seasonal pattern. The community structure of bacteria and the species composition of fungi in PM2.5 showed significant seasonal variations. The dominant bacteria were Actinobacteria (33.89%), Proteobacteria (25.72%), Firmicutes (19.87%), Cyanobacteria/Chloroplast (15.34%), and Bacteroidetes (3.19%), and Ascomycota, with an average abundance of 74.68% of all sequences, were the most abundant fungi. At the genus level, as many as 791 bacterial genera and 517 fungal genera were identified in PM2.5 . The results advance our understanding of the distribution and variation of airborne microorganisms in the metropolitan surrounding areas. Highlights: The microbial communities in spring samples showed the highest species richness. Bacterial species richness and diversity decreased with increase in air pollution. The community structure of bacteria in PM2.5 showed significant seasonal variations. The species composition of fungi in PM2.5 also showed significant seasonal variations. The study reveals the distribution of airborne microorganisms in suburban Beijing.